Nepalese legal standard of milk and common milk products and its implications - Upadhyay, Namdev; Khanal, Bipisha; Acharya, Yogendra; Timsina, Krishna Prasad (Journal of Agriculture and Natural Resources, 2021)
The milk and milk products are diversified and there is increasing awareness about the quality standards of products among the consumers.Therefore this study reviewed the legal standard of milk and common milk Products in Nepal and its implications using desk review and exploratory research.In Nepal, the department of food technology and quality control has developed several legal standards for the quality assurance of milk and milk products. National Dairy Development Board has established the Code of Practice for Dairy Industry 2004 which directs six criteria for the standardization of milk and milk products like Organoleptic test, Clot On Boiling (COB) test, Alcohol Test,Fat test and Solids-Not-Fat (SNF)test, Adulteration test, phosphate test, and microbial and coliform test. The review identified the quality standards of milk products like ghee, butter, paneer, milk powders but some quality parameters for ice-creams and cheese are still missing. The research identifies the quality non-compliance rate of milk and milk products that is about 19% which is in a decreasing trend. To the effective implementation of the legal standards, maintenance of health and hygiene of livestock at the production site, lab and infrastructure support at the distribution site, and creating consumer awareness to the consumer site is imperative.